Barista Memes - Boudreau Graham, Elise (Cuizine, 2018)
Last year during a particularly hard winter I was invited to a (now defunct) private Instagram chat group of femme and trans baristas.  We logged on mornings at 6AM to wish one another a good morning and swapped anecdotes of misogyny and appalling customer behaviour in the workplace.  I considered this a form of free group therapy. Another coping strategy I used was making memes at work. To ferment is to seethe with agitation or excitement, to work up, or to incite (trouble or disorder).  I’m not supposed to ferment at work.  My memes are about what I wish I could say to customers but am unable to do because my position in customer service requires amenability and a friendly attitude.  My Instagram account becomes a repository for the frustrations and anxieties that arise during a shift. I can post flippant content on the internet without feeling the need to contextualize or provide nuance because I have an audience who shares similar politics and/or work experiences.